The Development of School and Community Relationship Management,Dongphayungsongkroh School Under Kalasin Primary Educational Service Area Office 1 - Phuhongthong, Yutthaya; Khajornpanyapaisan, Komsan; Duangnet, Supot (Journal of Education Rajabhat Maha Sarakham University, 2024)
The objectives of this research were 1) to study the problems of the relations between the school and the community management, Dong Phayungsongkroh school under the kalasin primary educational service area office 1, 2) study the guidances of the school relationship, 3) study the results of the school and the community relationship management. The target group consisted of 6 co-researchers, key contributors, and 19 informants which using the principles of action research based on the conceptual framework of Kemmis and McTaggart as an implementation process. Observation and reflection research tools were a meeting minutes and an interview form. The research data analysis used the content analysis and presented data descriptively. The results of the research were as follows: 1. The results of the study on the management problems found that there was not the community service, public relations; school personnel focus on teaching and therefore there was not provide full services. Supplies was not readily available for community. There was not enough budget to support community services. Some community groups did not aware the importance of engaging with their children, especially in regard to behavioral problems solving which was largely given to the responsible teachers. The school representatives had attended some community events. Some teachers did not attend their community activities. Teachers were stuck with the main tasks of organizing instruction, and there was not assignments or instructions to perform public relations tasks that mediate the school with the community. 2. The guidelines for relationships development consisted of 4 development approaches, which were as follows: 1) participatory workshop, 2) teamwork 3) academic trip, and 4) co-development supervision. 3. According to the results of the relationship management after the school used the relationship development plan in various aspects, found that the strengten policies was determined to facilitate and service the people in communities, these facilitated the people. There was specified the responsible staffs, readiness all facilities, the Basic Education Commission Community Assistance Board committees and students’ parents participated the school meetings, there was a good communication, so they collaborated the school policies to develop the students, there was a better and obvious public relation to the communities, the people in communities awared and participated the school activities.